Comparison of the effectiveness of intra-infrapatellar fat pad and intra-articular glucocorticoid injection in knee osteoarthritis patients with Hoffa’s synovitis: protocol for a multicentre randomised controlled trial - Yiwei Chen; Changqing Zhang; Tao Gao; Hongyi Zhu; Qiuke Wang; Qianying Cai; Junqing Lin; Jiali Lin; Longxiang Shen (BMJ Open)
Introduction The infrapatellar fat pad and synovium are the sites of immune cell infiltration and the origin of proinflammation. Studies have shown that Hoffa’s synovitis may be a sign of early-stage osteoarthritis (OA). However, there have been no effective interventions specifically for Hoffa’s synovitis.Methods and analysis We will conduct a multicentre, multi-blind (participant, physician, outcome assessor and data analyst blinded) randomised controlled trial to compare the effectiveness of an intra-infrapatellar fat glucocorticoid versus an intra-articular injection for Hoffa’s synovitis in patients with knee OA. We will recruit 236 knee OA patients with Hoffa’s synovitis at outpatient clinics in three centres. We will randomly allocate them to two groups in a 1:1 ratio. One group will receive ultrasound-guided injection of 40 mg (1 mL) triamcinolone acetonide into the infrapatellar fat pad; the other group will receive ultrasound-guided injection of 40 mg (1 mL) triamcinolone acetonide into the knee joint cavity. All patients will be followed up at 2, 4, 8, 12 and 24 weeks after the injection. Primary outcomes are (1) Hoffa’s synovitis improvement rate, measured with the MRI Osteoarthritis Knee Score system (superiority outcome) at 24 weeks and (2) pain intensity, measured with the Western Ontario and McMasters University Osteoarthritis Index (WOMAC) at 2 weeks post-injection. Secondary outcomes include Hoffa’s synovitis score at 2 weeks post-injection, pain intensity with the numerical rating scale, WOMAC questionnaire score improvements (function, joint stiffness and total score), improvement rates in effusion synovitis at 2 and 24 weeks, articular cartilage thickness changes at 2 and 24 weeks, Intermittent and Constant Osteoarthritis Pain score, quality of life measured with the EuroQol-5D, OARSI-OMERACT response indicators, co-interventions and side effects at 2, 4, 8, 12 and 24 weeks.Ethics and dissemination Ethical approval has been granted by the Medical Ethics Committee of the Shanghai Sixth People’s Hospital Affiliated to Shanghai Jiao Tong University School of Medicine (2023–178). Written informed consent will be obtained from all patients prior to data collection. The findings of this research will be shared through presentations at academic conferences and publications in peer-reviewed journals.Trial registration number ChiCTR2400080474.